Short-term plasticity of the motor cortex compensates for bradykinesia in Parkinson’s disease - Guerra, Andrea; Colella, Donato; Cannavacciuolo, Antonio; Giangrosso, Margherita; Paparella, Giulia; Fabbrini, Giovanni; Berardelli, Alfredo; Bologna, Matteo (Neurobiology of disease, 2023)
Patients with Parkinson's disease (PD) show impaired short-term potentiation (STP) mechanisms in the primary motor cortex (M1). However, the role played by this neurophysiological abnormality in bradykinesia pathophysiology is unknown. In this study, we used a multimodal neuromodulation approach to test whether defective STP contributes to bradykinesia. We evaluated STP by measuring motor-evoked potential facilitation during 5 Hz-repetitive transcranial magnetic stimulation (rTMS) and assessed repetitive finger tapping movements through kinematic techniques. Also, we used transcranial alternating current stimulation (tACS) to drive M1 oscillations and experimentally modulate bradykinesia. STP was assessed during tACS delivered at beta (β) and gamma (γ) frequency, and during sham-tACS. Data were compared to those recorded in a group of healthy subjects. In PD, we found that STP was impaired during sham- and γ-tACS, while it was restored during β-tACS. Importantly, the degree of STP impairment was associated with the severity of movement slowness and amplitude reduction. Moreover, β-tACS-related improvements in STP were linked to changes in movement slowness and intracortical GABA-A-ergic inhibition during stimulation, as assessed by short-interval intracortical inhibition (SICI). Patients with prominent STP amelioration had greater SICI reduction (cortical disinhibition) and less slowness worsening during β-tACS. Dopaminergic medications did not modify β-tACS effects. These data demonstrate that abnormal STP processes are involved in bradykinesia pathophysiology and return to normal levels when β oscillations increase. STP changes are likely mediated by modifications in GABA-A-ergic intracortical circuits and may represent a compensatory mechanism against β-induced bradykinesia in PD. •Parkinson's disease patients demonstrated impaired short-term potentiation (STP).•The degree of STP impairment correlated with movement velocity and amplitude.•Beta-transcranial alternating current stimulation (tACS) restored STP in patients.•Beta-tACS-related improvements in STP were linked to changes in movement slowness.•Beta-tACS-related changes in STP were also related to GABAergic inhibitory activity.